1002. Complex Outpatient Antimicrobial Therapy (COpAT) Program at a Rural Academic Medical Center: Evaluation of First 100 Patients. (15th December 2022) - Juskowich, Joy J; Ward, Andrew; Spigelmyer, Amy E; Howard, Catessa A; Slain, Douglas; Guilfoose, John A; Edmond, Michael B; Sarwari, Arif R
Abstract: Background: Literature shows early intravenous (IV) to oral (PO) antimicrobial transition for infective endocarditis (IE) and bone and joint infection (BJI) is noninferior to prolonged IV antimicrobial therapy. COVID-19 pandemic peaks resulted in critical shortages of staffed hospital beds spurring innovation. Outpatient parenteral antimicrobial therapy (OPAT), a well-established program using prolonged IV antimicrobials, faces challenges such as infusion resource needs and social circumstance limitations. Complex outpatient antimicrobial therapy (COpAT) uses PO in place of IV antimicrobials. We hypothesized rapid adoption of COpAT would decrease hospital length of stay and open beds while retaining satisfactory clinical outcomes. Methods: COpAT protocols (Image 1) and guidelines by infection type and isolated organism (Image 2) were created. Hospitalized patients including persons who inject drugs (PWID) were evaluated for IV to PO antimicrobial transition by an infectious diseases (ID) physician and then followed by an ID physician-pharmacist team. Demographic, ID, and clinical outcome data for the first 100 COpAT patients between December 2020 and February 2022 were obtained by retrospective chart review. Image 1. COpAT Inpatient and Outpatient Protocols Image 2. COpAT Guidelines by Infection Type and Isolated Organism MSSA = methicillin-susceptible Staphylococcus aureus; MRSA = methicillin-resistant Staphylococcus aureus; spp. = species; TMP/SMX = trimethoprim-sulfamethoxazole; DS = double strength; SSTI = skin and soft tissue infection; CAP = community-acquired pneumonia Results: PWID accounted for 78% of COpAT patients. BJI followed by mixed infection (IE and BJI) was most prevalent (Image 3) with bacteremia in 53% of cases. Staphylococcus aureus was most frequently isolated (Image 4). Oral linezolid and fluoroquinolones, often in combination, were most commonly used. IV and PO antimicrobials were taken for a median 28 and 14 days, respectively. The COpAT program saved 1425 IV antimicrobial and 1363 hospital days. Assuming daily inpatient cost of $2050, cost avoided was $2, 794, 150. COpAT patients participated in ID follow-up and adhered to PO antimicrobials with low 30-day readmission rates (Image 5). Image 3. Infection Type Image 4. Isolated Organism CoNS = coagulase-negative staphylococci Image 5. Clinical Outcomes Conclusion: In a sample of 100 COpAT patients including PWID, IV to PO antimicrobial transition safely saved hospital days and mitigated critical bed shortages during pandemic peaks. A successful COpAT program requires a multidisciplinary group: close ID physician-pharmacist collaboration extending to OPAT and antimicrobial stewardship teams. With a COpAT program in place, even earlier IV to PO antimicrobial transitions should be studied. Disclosures: All Authors : No reported disclosures.